Neurochemistry: the basis of psychopharmacology - Henn, Fritz A.; Hitzemann, Robert (Contemporary psychiatry, 2001)
For ages, man has taken psychic comfort in the effects of drugs such as alcohol, morphine and cocaine. However, it was not until the 1950s that drugs became available with a demonstrated efficacy in the treatment of psychiatric disorders such as schizophrenia and depression. Attempts to understand the mechanisms of action for these drugs have been essential in the development of modern concepts in biological psychiatry. For example, the dopamine (DA) hypothesis of schizophrenia largely derives from experiments showing that antipsychotic drugs such as haloperidol and chlorpromazine affect the metabolism of DA but not other neurotransmitters (although at the time this hypothesis was formulated in the early 1960s, there were relatively few “other” neurotransmitters). Roles for norepinephrine (NE) and serotonin (5-HT) in depression developed from the observation that reser-pine produces a “depressed” behavior in rodents and humans which is associated with the depletion of these transmitters.